PP72 Associations between active travel and weight and hypertension in six Lower and Middle Income Countries: a cross-sectional study. (2nd September 2014) - Laverty, AA; Palladino, R; Lee, JT; Millett, C
Abstract : Background: Although active travel (walking and cycling) is increasingly touted as an effective strategy to reduce noncommunicable diseases (NCDs) globally, there is little published data on the potential health benefits in lower and middle-income countries (LMICs). This study examined: (1) socio-demographic correlates of walking or cycling for travel; (2) associations between active travel and overweight and hypertension. Methods: Data come from the World Health Organisation Study on Global Ageing and Adult Health (SAGE) of China, India, Mexico, Ghana, Russia and South Africa. Data come from 40, 687 respondents to the survey between 2007 and 2010, aged 18 years and older, selected using a stratified random cluster design. Being overweight was defined using nurse-measured height and weight. Hypertension was defined as ≥140/90 mm Hg from three nurse measured blood pressures. Active travel for at least 30 min a day was categorised based on the question "How much time would you spend walking or bicycling for travel on a typical day?" Logistic regression assessed associations between active travel and socio-demographic factors, as well as likelihood of being overweight or having hypertension. Analyses were adjusted for age, sex, marital status, time in education, living in an urban or rural area, minutes of work and leisure physical activity and household wealth, as well as smoking and fruit/vegetable consumption. Results: 56.8% of the sample undertook active travel for at least 30 min a day, ranging from 30.3% in South Africa to 73.0% in Russia. In pooled analyses those in wealthier households were less likely to use active travel (Adjusted Odds Ratio (AOR) 0.66, p < 0.001 for wealthiest fifth versus poorest), although this was not universally true (e.g. AOR 0.84, p = 0.621 for Mexico). Use of active travel for at least 30 min a day was associated with a lower likelihood of being overweight (AOR 0.79, p = 0.001), although effects varied, from AOR 0.54, p < 0.001 (Ghana) to AOR 1.12, p = 0.739 (South Africa). Active travel was associated with reduced odds of having hypertension in pooled analyses (AOR 0.84, p = 0.019) although results from individual countries were not statistically significant. Conclusion: Use of active travel is more common among those from lower socio-economic groups in most LMICs studied and appears to confer similar health benefits to those identified in high income settings. Efforts to maintain active travel levels should be integral to strategies to maintain healthy weight and prevent NCDs in LMICs.